ANALYSIS OF CHANGES TO THE POLICE CODE OF ETHICS SANCTIONS FOLLOWING THE ISSUANCE OF POLICE REGULATION NO. 7 OF 2022 - Avy Sena Putra Manggala; Sukmareni (Awang Long Law Review, 2026)
Sanctions for police officers who violate the KEPP were previously regulated in Regulation of the Chief of the Indonesian National Police Number 14 of 2011 concerning the Code of Ethics for the Indonesian National Police. However, this regulation has been revoked and replaced with Perpol Number 7 of 2022. Based on the considerations in letter c of Perpol No. 7 of 2022, the reason for revoking and replacing the previous provisions was that they were no longer in line with developments in ethical values, culture, and behavior in society that influence the behavior of Indonesian National Police officials. The data analysis used is normative juridical. The research approach used by the author is the legal approach. Changes in the police code of ethics sanctions after the issuance of Perpol No. 7 of 2022 include a clearer and more detailed separation between ethical sanctions and administrative sanctions, changes in nomenclature, the categorization of sanctions, and an increase in the number of sanctions. Analysis of changes in the police code of ethics sanctions after the issuance of Perpol No. 7 of 2022. The separation between ethical sanctions and administrative sanctions, coupled with changes in nomenclature that are easy to understand, clear, and even accessible to all citizens, is in line with legal certainty, which contains values that are very important in the context of law and justice. The principle of proportionality prevents penalties that are too severe or too lenient, which are not in line with the characteristics of police officers who violate the KEPP. The current sanctions are in line with the principle of balance, which, in theory, emphasizes the possibility of self-improvement.